The Maximum Demand Calculation System Analysis using MATLAB - Aidil, NorNabila; Mohd Jamail, Nor Akmal; Kamarudin, Qamarul Ezani (Evolution in Electrical and Electronic Engineering, 2023)
The project aims to develop a graphical user interface (GUI) tool for maximum demand calculation analysis. In today’s energy landscape, effective management of maximum demand is crucial for ensuring the reliable and efficient operation of electrical systems. The GUI will provide a visually appealing and interactive interface, enabling users to input relevant data, analyze power consumption patterns, and obtain accurate maximum demand calculations, by automating the calculations and streamlining the workflow, the GUI tool will significantly reduce the time and effort required to perform maximum demand analysis. The challenge faced by electrical engineers and utility companies in precisely estimating the maximum power demand within a specific time frame is the focus of this project’s issue statement. Maximum demand is important for capacity planning, load forecasting, and infrastructure design, among other power system management tasks. This project has successfully obtained the data from loads that are commonly used in an industry. The loads that have been used in this project were the contents of lighting, motors, pumps, compressors, and workshop equipment. Then, the graphical user interface (GUI) tool for maximum demand calculation analysis has been developed using MATLAB App Designer. Throughout the project, it has followed a systematic approach to achieve the objectives. It has begun by conducting a comprehensive literature review to understand the existing methods and techniques used in maximum demand calculation. Based on the research findings, the project designed and implemented an intuitive GUI that allowed users to input relevant data, such as load profiles, power consumption patterns, and timeframes. Then, it was developed by the necessary algorithms and mathematical models to process the input data and perform the maximum demand calculation. The implementation accurately considers peak loads, quantity of load, and various other factors that impact the maximum demand determination process. Moreover, to validate the accuracy and effectiveness of the system, the extensive testing and evaluation has been conducted. From the test, the maximum demand of the pumps for 10 days of usage is 12.95kW. In addition, the system conclusion from the load was Total cost of 10th June 2023 is RM468453.30 during peak time and RM464956.80 during off-peak time. The maximum demand cost is RM459725.00 for the total connected load in both conditions.